Critical Thinking Values in Religious Narratives: CDA of ELT Learning Materials for Young Learners - Wahyuni, Irma; Syihabuddin, Syihabuddin; Gunawan, Wawan; Darazi, Mansoor Ali (Register Journal, 2024)
This study examines the use of religious narratives, specifically the story of "Ibrahim, the Father of Prophets," from the bilingual collection Nabi & Rasul Allah (2018), to cultivate critical thinking among young English language learners in Indonesia. This study explores how the morals and language of a story can foster critical thinking in young students. Employing Fairclough's model of critical discourse analysis (CDA) and the transitivity framework of Systemic Functional Linguistics (SFL), the research investigates the critical thinking skills embedded in the English version of the Ibrahim story. The analysis includes a discourse-based examination of the story’s strategies and social practices, supplemented by interviews with English as a Foreign Language (EFL) teachers in Indonesian religious elementary school. This integrated approach highlights the role of critical thinking in selecting appropriate learning materials and emphasizes socio-cultural contributions of religious narratives to material development and instructional design in ELT to young learners. The paper concludes that integrating moral values into English teaching does not negate the necessity of fostering critical thinking. Teachers can use critical thinking to select stories that enhance students' moral understanding and linguistic proficiency. This research contributes to ongoing discussions on the use of storytelling in education and provides insights into effective pedagogical strategies for incorporating critical thinking into ELT for young learners.